2008
DOI: 10.1300/j194v06n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Grandparenting Responsibility Among Elderly Asian Americans

Abstract: This study examines whether Asian American grandparents who reside with grandchildren take on responsibility for most of the basic needs of their grandchildren. We use data from the 2000 U.S. Census, which asked about grandparent responsibility for the first time. Younger grandparents, grandparents without disabilities, and grandmothers are more likely to be responsible for their grandchildren. Those who immigrated at age 65 or older are less likely than native grandparents to be responsible for their grandchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In some cases, they could provide childcare to their grandchildren, freeing their children to work or save on maids or day-care (e.g., Phua and Kaufman, 2008;Baydar and Brooks-Gunn, 1998). Some elderly who live with their families also help with housecleaning, grocery shopping and preparation of food.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, they could provide childcare to their grandchildren, freeing their children to work or save on maids or day-care (e.g., Phua and Kaufman, 2008;Baydar and Brooks-Gunn, 1998). Some elderly who live with their families also help with housecleaning, grocery shopping and preparation of food.…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey conducted in the United States and 23 European countries, the generational transition from parents to grandparents typically starts in the fifth decade of life, and by the age of 70 more than 80% become grandparents (Leopold & Skopek, 2015). A survey of Asian Americans revealed that most grandparents responsible for raising grandchildren were in their 60s (Phua & Kaufman, 2008). However, major transformations in mental and physical health start to occur in the fifties.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has already showed that, after migration, children become cultural experts more rapidly than adults (Kenner et al, 2007;Orellana, 2009), highlighting major discrepancies between the traditional roles that adults played before migration and those available to them post-migration. Reduced social networks or limited ability to speak or read the new language affect adults' ability to maintain 'expert' roles (Phua & Kaufman, 2008), as is their potentially more limited knowledge about the new social systems (Gadsden & Simmons, 1996;Yoshida, Gordon, & Henkin, 2008). In the case of ethnic minority children, developing a cultural identity under the influence of one or more cultural groups transcends the formal and informal spaces and involves them in constant processes of negotiating expectations in a battleground of (mainly adult) influences.…”
mentioning
confidence: 99%